The Effect of Pursed Lips Breathing Exercises and Diafragma Breathing on Spirometry and Modified Medical Research Council Scale on Stable Chronic Obstruction Lung Disease - Ida Muna Junita; Mulyadi Mulyadi; Teuku Zulfikar; Nurrahmah Yusuf (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2021)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a chronic disease characterized by limited airflow and a chronic inflammatory response to the airways, where shortness of breath is the main complaint in COPD patients. Pursed lips breathing (PLB) and diaphragmatic breathing exercises are useful techniques to improve ventilation by increasing the Forced Expiratory Volume 1 (FEV1) value and decreasing the degree of shortness of breath. This study aims to determine the effect of pursed lips breathing and diaphragmatic breathing exercises on the improvement of lung function and the degree of shortness of breath in stable COPD patients. Methods: This is an experimental study with pre-test and post-test control group methods of 60 stable COPD patients at the RSUDZA Pulmonology Clinic from November 2019 to February 2020. The sample was taken by systematic random sampling, divided into 2 groups, namely the intervention group who received training. PLB and diaphragmatic breathing exercises for 4 weeks coupled with indacaterol bronchodilator therapy. The control group only received indacaterol therapy. Changes in lung function were assessed by spirometry, namely FEV1 and Forced Vital Capacity (FVC) values and changes in the degree of shortness of breath using the mMRC scale. Statistical analysis used was t-test and Wilcoxon test, which were performed to assess differences between groups, the value of significance (P<0.05). Results: There was a significant effect on FEV1 (P=0.0005) and FVC (P=0.014) in the intervention group compared to the control group. There was a significant effect on improving the degree of shortness of breath using the mMRC scale in the intervention group compared to the control group (P=0,0005). Conclusion: The administration of PLB and diaphragmatic breathing exercises significantly increased FEV1, FVC and improved the degree of shortness of breath. It is suggested that this exercise can be used as an adjunct therapy in COPD patients.